1995
DOI: 10.1093/jnci/87.18.1400
|View full text |Cite
|
Sign up to set email alerts
|

Anti-p53 Antibodies in Sera of Workers Occupationally Exposed to Vinyl Chloride

Abstract: Serum anti-p53 antibodies can predate clinical diagnosis of certain tumors, such as ASL, and may be useful in identifying individuals at high cancer risk, such as workers with occupational exposure to vinyl chloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 0 publications
3
61
1
1
Order By: Relevance
“…Antibodies to p53 protein have never been detected in the serum of healthy subjects (Rosenfeld et al, 1997). In some cases, anti-p53 antibodies were found in the serum of cancer patients before clinical manifestation of disease (Schlichtholz et al, 1994;Lubin et al, 1995;Trivers et al, 1995). Trivers and co-workers determined the presence of anti-p53 antibodies 4 months, in particular even 11.3 and 10.8 years, before diagnosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to p53 protein have never been detected in the serum of healthy subjects (Rosenfeld et al, 1997). In some cases, anti-p53 antibodies were found in the serum of cancer patients before clinical manifestation of disease (Schlichtholz et al, 1994;Lubin et al, 1995;Trivers et al, 1995). Trivers and co-workers determined the presence of anti-p53 antibodies 4 months, in particular even 11.3 and 10.8 years, before diagnosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These data showed that presence of antibodies against six of these antigens was a good diagnostic classifier for prostate cancer. Importantly, it has also been observed that antibody responses to p53 were diagnostic for asymptomatic liver tumours in individuals that were exposed to toxic compounds [76]. Strikingly, these antibody responses could even predate clinical diagnosis of oesophageal cancer [77].…”
Section: Early Detection Of Cancermentioning
confidence: 99%
“…Anti-p53 serum antibodies have been associated with poor prognosis and advanced stage in breast (Schlichtholz et al, 1992;Angelopoulou et al, 1996), head and neck (Bourhis et al, 1996), colorectal (Houbiers et al, 1995;Coomber et al, 1996) and ovarian (Angelopoulou et al, 1996;Gadducci et al, 1996) cancers. However, serological assessment of anti-p53 antibodies seems also to allow detection of tumours at an early and therefore more treatable stage (Lubin et al, 1995b;Trivers et al, 1995Trivers et al, , 1996. Moreover, this non-invasive test is adapted to the follow-up of cancer patients in clinical routine laboratories.…”
mentioning
confidence: 99%